The Symbolic Meaning of Culture in the Seven-Monthly Ceremony: CS. Peirce's Semiotic Perspective - Amri, Yusni Khairul (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The mitoni tradition or seven-month ceremony during the first pregnancy is part of Javanese culture that is rich in symbolic meaning, but the meaning of the symbols in this procession has not been studied in depth. The lack of exploration of the semiotic aspects of this procession has led to a gap in understanding the cultural and spiritual values contained within it. This study aims to analyze and interpret the symbolic meanings in the Seven-Month Ceremony, particularly in uncovering the triadic relationship between signs, objects, and interpreters. This is a qualitative study. The research subjects consist of 26 cultural symbols identified from the video of the Mitoni Aaliyah Massaid ceremony, comprising 15 plant-based symbols and 11 symbols from natural elements. Data was collected through visual observation of one main video using documentation techniques and structured observation guided by a symbol worksheet. Data analysis was conducted through the stages of data selection, symbol coding, content analysis, semiotic analysis, meaning interpretation, and conclusion drawing. The results of the study indicate that the symbols in the mitoni procession contain values of purity, protection, fertility, hope, and spirituality that reflect the worldview of Javanese society. The conclusion of this research affirms that the mitoni procession is a form of visual cultural communication that contains a complex system of signs and can be scientifically analyzed through triadic semiotics. The implications of this research support the preservation of cultural heritage and serve as a reference in the development of education based on local wisdom.